2011
DOI: 10.1002/adma.201100923
|View full text |Cite
|
Sign up to set email alerts
|

Organic−Inorganic Nanocomposites by Placing Conjugated Polymers in Intimate Contact with Quantum Rods

Abstract: Novel organic−inorganic nanocomposites are synthesized by directly grafting end‐functionalized conjugated polymers (CPs) onto anisotropic nanocrystals (NCs) that have a complimentary functional group through a robust Heck coupling. Such nanocomposites, in which CPs and anisotropic NCs are intimately contacted, are very promising for use in organic−inorganic hybrid solar cells with improved power conversion efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 43 publications
1
72
0
1
Order By: Relevance
“…It is found that a hybrid containing 80 wt% CdSe NTs could intensively quench the PL intensity of P3HT NWs, especially the main emission at 700 nm. This is interestingly the same with that of the organic polymer-grafted nanoparticles reported in ref [30]. The static PL result indicates that the photon-generated excitons could be efficiently dissociated through diffusing in the crystallized P3HT NWs and thereafter splitting at the hybrid interface.…”
Section: Resultssupporting
confidence: 88%
“…It is found that a hybrid containing 80 wt% CdSe NTs could intensively quench the PL intensity of P3HT NWs, especially the main emission at 700 nm. This is interestingly the same with that of the organic polymer-grafted nanoparticles reported in ref [30]. The static PL result indicates that the photon-generated excitons could be efficiently dissociated through diffusing in the crystallized P3HT NWs and thereafter splitting at the hybrid interface.…”
Section: Resultssupporting
confidence: 88%
“…Several capping strategies have emerged in the literature: the ligand exchange [15][16][17], the use of novel surfactants [18,19], the synthesis of NPs with thermally cleavable ligands [20], the synthesis of NPs in solutions of polymers [21,22], the polymerization of polymers on the surface of NPs [23], and the deposition of a polymer containing a soluble precursor of the NPs [24]. More details on the role of capping ligands/polymers can be found in recent works [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…Similar to organic solar cells, [35][36][37][38][39][40] two main morphologies of the active layers are found in literature, a planar and a bulk heterojunction (BHJ) geometry. [41][42][43][44][45][46][47] In a planar arrangement, the n-type and p-type materials have one more or less planar interface. In Principle processes occurring in hybrid solar cells.…”
Section: Fundamentals Of Hybrid Solar Cells Functionmentioning
confidence: 99%